Push back and pull down to socket manoeuvre – a simple and effective technique to engage graft into the tibial socket in all inside anterior cruciate ligament reconstruction - Thundathil, Sreejith; Madheswaran, Naveen; Sarath, Nidhin; Suresh, Nihal (International Journal of Research in Orthopaedics, 2026)
Background: All-inside Anterior cruciate ligament Reconstruction technique is newer technique that has advantages of preservation of cortical bone. The potential for peripatellar soft tissue to become interposed between the bone and the graft has been a significant issue in the technique. Early necrosis of any interposed tissue can compromise the strength of fixation button. Our technique of pushback and pull down to socket manoeuvre avoids this interposition and entanglement. This study was done to know the efficacy of pushback and pull down to socket manoeuvre. Methods: In our study, 298 cases fulfilling the criteria undergone All inside anterior cruciate ligament reconstruction with push back and pull down to socket manoeuvre and corresponding radiological and functional outcomes were assessed using International Knee Documentation Committee (IKDC) score. Results: In our study, the mean IKDC score is 83 at 1 year follow-up. There is no radiological widening of both femoral and tibial tunnel during follow up. There is considerable reduction of time for passing graft into the tibial socket. No episodes of entanglement happened in any case during surgery and the success rate was 100 percent. Conclusions: Push back and pull down to socket manoeuvre is a simple and fail proof technique to avoid peri patellar soft tissue entanglement while managing the engagement of graft into the tibial socket. This technique also helps to save time, improves surgeons comfort.